Sick - Leveen, Tom (Amulet Books, 2013)
Brian and his friends are not part of the cool crowd. They’re the misfits and the troublemakers—the ones who jump their high school’s fence to skip class regularly. So when a deadly virus breaks out, they’re the only ones with a chance of surviving.